THE ROLE OF THE SUMUT TEACHING MOVEMENT IN FORMING CHILDREN'S CHARACTER IN SIBOLANGIT - Zikra Fitriwa Adriani Aulia; Mohammad Al Farabi (UIN Sumatera Utara Medan, 2024)
This study aims to describe the role of the North Sumatra Teaching Movement in building the character of children in Sibolangit District, Deli Serdang Regency, as well as aspects of program activities, implementation, supporting factors and constraints faced. The method used in this research is a qualitative research method and the type of research is field research. Data collection techniques use triangulation techniques, namely observation, interviews and document studies. In analyzing the data, the Miles and Huberman technique was used which consisted of data reduction, data presentation and conclusion. Results pThe research in this thesis shows that the programs carried out in the Sumut Teaching Movement activities have five categories, namely education, social, religion, economy, and environment. In the education category there are disaster classes, inspiration, cultural arts, creativity, reading stops, and role plays. In the social category there are healthy afternoon classes, social services, and healthy clean living. Furthermore, in the religion category there are classes on reciting the Koran, praying five times a day, and attending recitations. Then in the economic category there is a creative economy class, while in the environmental category there are the eco brik program and waste cruising. The implementation of the program is carried out continuously and added special implementation for 18 days. The supporting factors for this movement are the support from the government, community, community leaders, and formal institutions.